2014
DOI: 10.1109/lpt.2014.2332000
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Wavelength, Bidirectional Single-Wall Carbon Nanotube Mode-Locked Fiber Laser

Abstract: A fiber ring laser with a carbon nanotube modelocker that allows bidirectional oscillation is experimentally demonstrated in the L-band. Through leveraging a double-peak intracavity gain spectrum, two pulse trains in two nonoverlapping wavelength bands are shown to counter-propagate in the simple ring cavity. Ultrashort soliton pulses of ∼800 fs or less can be stably generated in both directions. It is also demonstrated that bidirectional operation within one of the wavelength bands can also be achieved with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…While traveling along the same physical path, chromatic or polarization-mode dispersion results in different roundtrip time from one cavity. Multi-pulse lasing had also been observed in bidirectionally oscillating cavities [13,14] or a unidirectional one with slightly different beam paths [15].…”
Section: Introductionmentioning
confidence: 93%
“…While traveling along the same physical path, chromatic or polarization-mode dispersion results in different roundtrip time from one cavity. Multi-pulse lasing had also been observed in bidirectionally oscillating cavities [13,14] or a unidirectional one with slightly different beam paths [15].…”
Section: Introductionmentioning
confidence: 93%
“…Up to now several schemes of bidirectional ML fiber lasers have been successfully demonstrated [2,[4][5][6][7][8][9]. Some of them exploit the pure ring cavity design [2,[4][5][6], but the others contain a four-port circulator for independent control of clockwise (CW) and counterclockwise (CCW) pulses [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Some of them exploit the pure ring cavity design [2,[4][5][6], but the others contain a four-port circulator for independent control of clockwise (CW) and counterclockwise (CCW) pulses [7][8][9]. It should be stressed that the vast majority of these lasers generate conservative solitons (CSs) with ∼600 fs∕1 ps duration in both CW and CCW directions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, recent results demonstrated that the ultrafast fiber laser could be mode locked in a bidirectional manner [19][20][21]. In this case, the lightwaves propagate in two opposite directions in the same laser cavity, indicating that they share the same gain medium, saturable absorber and net dispersion.…”
mentioning
confidence: 99%